Filosofia e criação na escola: entre estrato e linha de fuga - Jair Miranda de Paiva (EccoS – Revista Científica)
Abstract: This text aims to deliberate about the power of school as stratum, even though they constitute one of the micropowers that, through discipline, punishment and examination, conforms bodies and subjectivities, can, however, become condition of another school as plant ideas such as studio experimentation. It is deliberated the deleuzian concept of virtual possibilities of thinking about creation in school, unlike the catastrophic thoughts about his impending end, as well as their inadequacy to the present time. The juncture point of these two angles is constituted by a statement about the strata in A Thousand Plateaus: “Isn’t it required to save a minimum of layers, a minimum of forms and functions, a minimum of subjects to extract material affects, and assemblages?” (DELEUZE; GUATTARI, 1997, p. 60).